Impact of the COVID-19 pandemic on the disease course of patients with inflammatory rheumatic diseases: results from the Swiss Clinical Quality Management cohort. Issue 2 (22nd September 2020) - Ciurea, Adrian; Papagiannoulis, Eleftherios; Bürki, Kristina; von Loga, Isabell; Micheroli, Raphael; Möller, Burkhard; Rubbert-Roth, Andrea; Andor, Michael; Bräm, René; Müller, Angela; Dan, Diana; Kyburz, Diego; et al.
Abstract : Objectives: To investigate whether the transient reduction in rheumatology services imposed by virus containment measures during the COVID-19 pandemic was associated with disease worsening in axial spondyloarthritis (axSpA), rheumatoid arthritis (RA) or psoriatic arthritis (PsA). Methods: Patient-reported disease activity assessed during face-to-face visits and/or via a smartphone application were compared between three periods of each 2 months duration (before, during and after the COVID-19-wave) from January to June 2020 in 666 patients with axSpA, RA and PsA in the Swiss Clinical Quality Management cohort. Results: The number of consultations dropped by 52%, whereas the number of remote assessments increased by 129%. The proportion of patients with drug non-compliance slightly increased during the pandemic, the difference reaching statistical significance in axSpA (19.9% vs 13.2% before the pandemic, p=0.003). The proportion of patients with disease flares remained stable (<15%). There was no increase in mean values of the Bath Ankylosing Disease Activity Index, the Rheumatoid Arthritis Disease Activity Index-5 and the Patient Global Assessment in patients with axSpA, RA and PsA, respectively. Conclusion: A short interruption of in-person patient–rheumatologist interactions had no major detrimental impact on the disease course of axSpA, RA and PsA as assessed by patient-reported outcomes.